NKG2D ligand overexpression in lupus nephritis correlates with increased NK cell activity and differentiation in kidneys but not in the periphery - Spada, Roberto; Rojas, Jose´ M.; Pe´rez‐Yagu¨e, Sonia; Mulens, Vladimir; Cannata‐Ortiz, Pablo; Bragado, Rafael; Barber, Domingo F. (Journal of leukocyte biology, 2015)
NKG2D ligand expression, NK cells, and cytokine expression by NK cells could play a role in the lupus nephritic process. NK cells are a major component of the immune system, and alterations in their activity are correlated with various autoimmune diseases. In the present work, we observed an increased expression of the NKG2D ligand MICA in SLE patients’ kidneys but not healthy subjects. We also show glomerulus‐specific expression of the NKG2D ligands Rae‐1 and Mult‐1 in various murine SLE models, which correlated with a higher number of glomerular‐infiltrating NK cells. As the role of NK cells in the immunopathogenesis of SLE is poorly understood, we explored NK cell differentiation and activity in tissues and organs in SLE‐prone murine models by use of diseased and prediseased MRL/MpJ and MRL/lpr mice. We report here that phenotypically iNK cells accumulate only in the spleen but not in BM or kidneys of diseased mice. Infiltrating NK cells in kidneys undergoing a lupus nephritic process showed a more mature, activated phenotype compared with kidney, as well as peripheral NK cells from prediseased mice, as determined by IFN‐γ and STAT5 analysis. These findings and the presence of glomerulus‐specific NKG2D ligands in lupus‐prone mice identify a role for NK cells and NKG2D ligands in the lupus nephritic process, which could aid in understanding their role in human SLE.